2018
DOI: 10.3390/coatings8110383
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Corrosion Protection of Iron by Poly(3-hexylthiophene)/Poly(styrene-co-hydroxystyrene) Blends

Abstract: Corrosion of iron in NaCl solution is significantly reduced by poly(3-hexylthiophene) (P3HT)/poly(styrene-co-hydroxystyrene)(PS-co-PHS) blended coating layers, especially at elevated temperature. The interaction between sulfur (in P3HT) and hydroxyl group (in PS-co-PHS) leads to enhanced miscibility between P3HT and PS-co-PHS and results in improved thermal stability upon thermal treatment. Adhesion force between iron and the coating layer is increased with increasing hydroxystyrene ratio as revealing by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…PTPA-C6 and PS- co -PHS were synthesized following the procedures described in the literature [ 37 , 38 ]. PTPA-C6 was synthesized by a reaction of 4-hexylaniline with dibromobiphenyl in anhydrous toluene ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PTPA-C6 and PS- co -PHS were synthesized following the procedures described in the literature [ 37 , 38 ]. PTPA-C6 was synthesized by a reaction of 4-hexylaniline with dibromobiphenyl in anhydrous toluene ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a conjugated polymer with specific functional group(s) that has good adhesion to the metal can serve as both a corrosion inhibitor and a passivation layer promoter. Based on this concept, a soluble poly triphenylamine (PTPA-C6) is synthesized and applied to the surface of iron substrate as a corrosion resistant coating by Tsai et al [ 37 ]. Functionality such as triphenylamine contains a nitrogen atom that has been proved to be effective in corrosion protection of metals.…”
Section: Introductionmentioning
confidence: 99%
“…P3HT/PMMA blend gave the best protraction to the steel. To enhance the interface interaction between different polymers in the blend, Huang et al [64] reported the preparation of P3HT/poly(styrene-cohydroxystyrene) blend (P-10 in Figure 6) via the intermolecular hydrogen bonding between thiophene and phenol group. The hydrogen bonding not only improved the miscibility between two polymers, but also enhanced the adhesion force between iron and coating layer.…”
Section: Sulfur-containing Synthetic Polymeric Inhibitormentioning
confidence: 99%